PREECLAMPSIA-ECLAMPSIA GRAVIDARUM AND THE DELIVERY OF THE CESAREAN SECTION METHOD - Suleman, Dewi M; Nurdin, Azizah; Setiawati, Dewi (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Introduction: Preeclampsia and eclampsia were emergencies, which greatly contribute to maternal mortality. The definitive management for preeclampsia-eclampsia gravidarum was pregnancy termination, which can be done by the caesarean section method.Purpose: To analyze the correlation between preeclampsia-eclampsia gravidarum and the caesarean section method at Prof. Dr. H. Aloei Saboe in September to January 2020.Method: Observational study with cross-sectional approaches. The sample used was mothers who gave birth at Prof. Dr. H Aloei Saboe during the period January-September 2020, which fulfilled the criteria of inclusion and exclusion with a total of 66 samples. Data were taken from medical records and analyzed by using the test Chi-square, with a significance value of 10% (Î± = 0.10).Results: Hypothesis testing used chi-square method with a level of significance 10% (Î± = 0.10), obtaining the p-value (0.82) ( p> 0.10).Conclusion: There was no significant correlation between preeclampsia-eclampsia gravidarum and the delivery of the Caesarean section method at Prof. Dr. H. Aloei Saboe January-September 2020 period